Halogen‐free solvent processed organic solar sub‐modules (≈55 cm2) with 14.70% efficiency by controlling the morphology of alkyl chain engineered polymer donor - Thavamani Gokulnath; Hyerin Kim; Donghyun Song; Ho‐Yeol Park; Je‐Sung Jee; Young Yong Kim; Jinhwan Yoon; Kakaraparthi Kranthiraja; Sung‐Ho Jin (EcoMat)
Abstract Goals of high efficiency, morphological analysis, and the ability to produce organic solar cell (OSC) sub‐modules using halogen‐free solvents are demanding. In this study, a robust conjugated polymer with thienothiophene π‐spacer with pendant alkyl side chain (NapBDT‐C12) was synthesized and used to fabricate sub‐modules. Excellent efficiencies were demonstrated by a NapBDT‐C12 integrated ternary blend, which was used to produce stable small‐area‐to‐sub‐module devices using O‐xylene. The efficiency of the NapBDT‐C12 added small‐area ternary devices (PM6:NapBDT‐C12:L8‐BO) was 18.71%. Owing to the controlled homogeneity of the blend with favorable nanoscale film morphology, enhanced carrier mobilities, and exciton dissociation/splitting properties, contributed to the efficiencies of small‐area‐to‐sub‐module OSCs. Moreover, a 55 cm2 sub‐module with an efficiency of 14.69% was accomplished by bar coating using O‐xylene under ambient conditions. This study displays the potential of a ternary blend based OSC device to produce high efficiency scalable sub‐modules at ambient conditions.